(3JGL GdeLGejYs - (3JGL GdOjf Hf CMeO Hf EHQGgje Hf JGL GdOjf Hf eMeO GdCfUGQj GdeOfj GdeGdcj,J (B1066 (3g` s
(3ChdgG (B:s
(3gPG eLehY bUOJ Cf CLeY ajg eG XaQJ Hg ef cdGe s
(3BNQgG (B:s
(3hde jJMOO ef GdCNHGQ aj gPg GdCbWGQ GdCbd SGQ hGdSdGe s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B82 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B87s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B210s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH (B- (3GdQHGW (B(D 602) s
Keywords: (3GdeYGQa GdYGeIs